Implementing Ambient Intelligence Using Supply Chain Management Based on Blockchain and Cloud Integration - Putri, Astrid Novita; Arif, Yunifa Miftachul; Wardhani, Anindya Khrisna; Hariadi, Mochamad; Rachmadi, Reza Fuad (KnE Life Sciences, 2025)
In agricultural supply chain management that the involvement of intermediaries in product distribution often leads to increased prices for agricultural goods. This study proposes a solution using Smart Contracts and Certificate Authority within a blockchain framework to streamline distribution channels and reduce the Bullwhip Effect. The research simulates collaboration between farmers and consumers by implementing smart agriculture practices and optimizing distribution through Hyperledger Fabric- based blockchain technology. Data are securely stored in a ledger accessible only to authorized participants. The system framework includes farmers as producers, Village Unit Cooperatives as intermediaries, distributors, and end consumers. Ambient Intelligence technology, based on supply chain management principles, supports real-time awareness, activity recognition, and responsiveness using RFID sensors. Each product is tagged with RFID for automatic identification and tracking of goods and stakeholders. RFID-collected data are used to analyze consumer behavior and monitor presence, while GPS provides real-time shipment tracking with location updates and estimated delivery times. All components are integrated with blockchain to ensure transparency and efficiency across the supply chain. Transactions are automated via smart contracts, enabling secure and efficient processes while ensuring data integrity through a peer-to-peer network of nodes that store cryptographic records.